Societal impact of recycling waste into composite materials - Fazlar Rahman (Societal Impacts)
Demands for consumer goods and synthetic materials have increased significantly due to rapid population growth. As a result, environmental pollution, natural disasters and catastrophes, and controlling and recycling waste have become crucial issues for global sustainability and developing a circular economy. Besides the various sources, solid waste is generated from medical fields, ready-made garment (RMG) industries, and human hair during their service time and life. Human hair, face masks, and RMG waste are disposed of in landfills, buried, and incinerated without recycling. It creates dust and microparticles and develops CO2, methane, and harmful gases before fully decomposing in landfills, promoting environmental hazards and degrading air quality and social attributes. In addition, it causes the infiltration of microplastics and other micro/nano-particles into aquatic life, birds, and animals, and ultimately into human organs through food chains. It can be controlled by reducing, reusing, and recycling waste into useful materials and resources. Therefore, scientists seek to replace synthetic materials by developing bio-composites through recycling waste. This study explores the social impact of recycling human hair, waste face masks, and RMG waste into composite fields, which will help to reduce environmental pollution and global warming, achieve sustainability, develop a circular economy, and deter climate change. In contrast to societal impacts, the scalability, cost-effectiveness, and long-term durability of composites will not be an issue since the cost of waste is tiny, composite's strengths are higher than some natural fiber-reinforced composites, and those wastes can also be used to fabricate hybrid composites as cheap constituents.